Selective processing of food - and body - related information and autonomic arousal in patients with eating disorders. - Perpiñá, Conxa; Treasure, Janet; Baños Rivera, Rosa Mª; Bond, Alyson; Leonard, Thierry (The Spanish Journal of Psychology, 1998)
Sin resumen